Location Site Selection Preferences of Construction Firms that Offer Second Homes to Foreign Investors: The Case of Trabzon - Ünlü Öztürk, Ceren; Türk, Ersin (ICONARP International Journal of Architecture and Planning, 2021)
Purpose Being necessarily proactive, spatial plans should consider national and global developments. In Turkey, after legislative amendments of the 2000s, legal obstacles for foreign investment in house-ownership were eradicated, raising a significant demand for second homes. If the current planning process does not turn this demand into an opportunity, it will probably be one of its main threatening factors. This study aims to uncover the criteria affecting the locational choices of construction companies for their project area in supplying second homes for those investors, and rank them according to their importance. Design/Methodology/Approach A three-stage AHP was utilized. First, the objectives, criteria and sub-criteria affecting the locational choices of construction companies were determined and a hierarchical structure was set. Secondly, pairwise comparisons were made with the company officials. Thirdly, the relative and general weights of the criteria and sub-criteria were calculated and locational preferences for the project area were uncovered. The city of Trabzon, where the second home supply for the citizens of the countries in Arabian Peninsula increased after 2012, was chosen as the case. Findings It is concluded that the development plan decisions are very effective in the locational selection of the project areas. The most important criteria in the selection process are found to be the nearby plan decisions, high unit/m2 sale price of flats, and plan decisions on the parcel, in turn. Moreover, the ones for the sub-criteria were found to be having nearby a CBD plan decision, development order, and having a nearby recreational area plan decision, in turn. Research Limitations/Implications Although there are many such construction companies, only two company officials volunteered to participate, yet the study still provides a basis for future work and an awareness for international dynamics of the city. Originality/Value The criteria affecting the locational choices of construction companies for their project area in supplying second homes for foreign investors were revealed and ranked. Pairwise comparisons in AHP were made simultaneously with the participants using a videoconference application, considering the risk of Covid-19. The study contributes to housing supply literature and guide spatial plans by introducing locational preferences of the firms.